PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN JAWILAN KABUPATEN SERANG - Lutfiya Illah; Achmad Nashrudin P (Universitas Bina Bangsa, 2021)
To achieve organizational goals, a government agency requires good and measurable performance. In order for employee performance to be achieved properly, intense communication between employees is required. In carrying out public service tasks according to the duties and functions of employees at the Jawilan District Office, Serang Regency, it requires a common perception so that the goals of the organization can be achieved. The common perception is created through communication between employees, which is called interpersonal communication. This study intends to examine the effect of interpersonal communication on employee performance at the Jawilan District Office. The method used is a quantitative approach, using data collection methods through questionnaires. The sampling technique used was the saturated sample technique where the sample was 40 people. The number of samples is the same as the total population. Furthermore, the study uses a test of validity and a test of reliability. The results showed that the effect of interpersonal communication consisting of openness, empathy, support and positive feeling was increased, thus increasing employee performance. Based on the results of the T-test calculations, the test results show that the significance value = 0.000 <0.05 or sig value <0.05 t arithmetic > t table (5.983> 2.024). This means that Ha is accepted, and HO is rejected, and the result of the correlation coefficient (R) is = 0.746, the relationship is very strong between Interpersonal Communication and Employee Performance at the Jawilan District Office, Serang Regency. And the results of the regression analysis show that there is a positive influence between the Interpersonal Communication variabel (X) and the Employee Performance variabel (Y) at the Jawilan District Office, Serang Regency, as shown by the regression equation Y = 6.929 + 0.652X